Applying Semantic Search and Large Language Models to Solve Assortment Gaps in E-Commerce - Tran, Ngoc Khiem (2025)
This thesis addresses the problem of assortment gaps in e-commerce, with a particular focus on the grocery retail sector. The main objective is to develop a robust and scalable solution for identifying missing or substitute products by leveraging semantic search techniques and large language models (LLMs).